Prediction of postoperative complications after hepatectomy with dynamic monitoring of central venous oxygen saturation - Shinya Ida; Yoshifumi Morita; Akio Matsumoto; Ryuta Muraki; Ryo Kitajima; Satoru Furuhashi; Makoto Takeda; Hirotoshi Kikuchi; Yoshihiro Hiramatsu; Hiroya Takeuchi (BMC Surgery, 2023)
Abstract Background The usefulness of static monitoring using central venous pressure has been reported for anesthetic management in hepatectomy. It is unclear whether intra-hepatectomy dynamic monitoring can predict the postoperative course. We aimed to investigate the association between intraoperative dynamic monitoring and post-hepatectomy complications. Furthermore, we propose a novel anesthetic management strategy to reduce postoperative complication. Methods From 2018 to 2021, 93 patients underwent hepatectomy at our hospital. Fifty-three patients who underwent dynamic monitoring during hepatectomy were enrolled. Flo Trac system was used for dynamic monitoring. The baseline central venous oxygen saturation (ScvO2) was defined as the average ScvO2 for 30 min after anesthesia induction. ScvO2 fluctuation (ΔScvO2) was defined as the difference between the baseline and minimum ScvO2. Postoperative complications were evaluated using the comprehensive complication index (CCI). Results Patients with ΔScvO2 ≥ 10% had significantly higher CCI scores (0 vs. 20.9: p = 0.043). In univariate analysis, patients with higher CCI scores demonstrated significantly higher preoperative C-reactive protein-to-lymphocyte ratio (7.51 vs. 24.49: p = 0.039), intraoperative bleeding (105 vs. 581 ml: p = 0.008), number of patients with major hepatectomy (4/45 vs. 3/8: p = 0.028), and number of patients with ΔScvO2 ≥ 10% (11/45 vs. 6/8; p = 0.010). Multivariate logistic regression analysis revealed that ΔScvO2 ≥ 10% (odds ratio: 9.53, p = 0.016) was the only independent predictor of elevated CCI. Conclusions Central venous oxygen saturation fluctuation during hepatectomy is a predictor of postoperative complications. Anesthetic management based on intraoperative dynamic monitoring and minimizing the change in ScvO2 is a potential strategy for decreasing the risk of post-hepatectomy complications.